The relationship between mothers’ characteristics and perception regarding the support of health workers for exclusive breastfeeding in Central Kaduagung Village Lebak Regency - Syifa Fauziyah; Nur Setiawati Rahayu (Sarana Ilmu Indonesia (salnesia), 2024)
Exclusive non Breastfeeding is one of the factor occur in babies, babies are susceptible to infectious diseasesThe incidence of infants and toddlers suffering from re. repeated infectious will result in the occurrence of toddlers with malnutrition and underweight. This study aims to determine the relationship between maternal characteristics and the support of health workers for exclusive breastfeeding. The design in this study using cross sectional with a questionnaire instrument. The number of samples in this study were 64 people using purposive sampling technique. The data analysis used was the Chi-Square statistical test to determine the relationship between variables. The results showed that there was a significant relationship between education (p = 0.007), knowledge (p = 0.000) and support from health workers (p = 0.000) with exclusive breastfeeding. Meanwhile, there was no significant relationship between occupation age (p = 0.055), (p=0.945) and parity (p=0.443) with exclusive breastfeedingResearch result show that there is a significant relationship between mother’s education, mothers’s knowledge, mother’s perception regerding the support of health workers. While there is no significant relationship between the mother’s age, job and parity with exclusive breastfeeding.